Analysis of protection spanning-tree protocol - Корнієнко, Б.Я.; Сулима, С.О. (Proceedings of National Aviation University, 2007)
Extraordinary sweeping of IT – development causes vulnerabilities and, thereafter, attacks that use these vulnerabilities. That is why one must post factum or even in advance speed up invention of new information security systems as well as develop the old ones. The matter of article concerns Spanning-Tree Protocol – the vivid example of the case, when the cure of the vulnerability creates dozen of new "weak spots".